Regional modeling of surface solar radiation, aerosol, and cloud cover spatial variability and projections over northern France and Benelux - G. Chesnoiu; I. Chiapello; N. Ferlay; P. Nabat; M. Mallet; V. Riffault (Atmospheric Chemistry and Physics)
Investigating the current and future evolution of surface solar radiation (SSR) is essential in the context of climate change and associated environmental issues. We focus on the influence of atmospheric aerosols, along with cloud cover and water vapor content, on northern France and Benelux in spring and summer. Our analysis relies on the National Centre for Meteorological Research–Limited Area Adaptation Dynamic International Development v6.4 (CNRM-ALADIN64) regional climate model at 12.5 km resolution, which includes an interactive aerosol scheme. A regional evaluation of 2010–2020 ALADIN hindcast simulations of clear-sky and all-sky SSR, clear-sky frequency, and aerosols, through comparison to coincident multi-site ground-based measurements, shows reasonable agreement. In addition, these hindcast simulations emphasize how elevated aerosol loads over Benelux and high cloud cover over southwestern England reduce the SSR. Additional ALADIN climate simulations for 2050 and 2100 under Coupled Model Intercomparison Project phase 6 (CMIP6) Shared Socioeconomic Pathway (SSP) 1-1.9 predict a significant reduction in aerosol loads compared to 2005–2014, especially over Benelux, associated with future increases in clear-sky SSR but geographically limited all-sky SSR evolution. In contrast, under SSP3-7.0, clear-sky and all-sky SSR is projected to decline significantly over the domain. This decline is greatest in spring over Benelux due to combined increases in cloud cover and nitrate aerosols projected from 2050 onwards. In summer, projected decreases in cloud cover largely attenuate the reduction in SSR due to aerosols in 2050, while by 2100 rising water vapor contents counteract this attenuation. Thus, our results highlight seasonally and spatially variable impacts of future anthropogenic aerosol emissions on SSR evolution due to cloud cover and water vapor modifications that will likely largely contribute to the modulation of forthcoming aerosol influences.